Composite catalyst for synergistically denitrifying and removing chlorine-containing organic matters as well as preparation method and application of composite catalyst

Metal oxide-based piezoelectric catalysts were prepared by ball milling and heterojunctions were constructed, solving the problem of synergistic removal of nitrogen oxides and chlorinated organic compounds at low temperatures, and achieving efficient and low-cost synergistic catalytic effects for multiple pollutants.

CN120393996AActive Publication Date: 2025-08-01ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510219584.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-08-01
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively and synergistically remove nitrogen oxides and chlorinated organic compounds from waste incineration flue gas under low-temperature conditions. The catalysts exhibit poor synergistic performance and low selectivity, resulting in high investment costs and large space requirements.

Method used

Metal oxide-based piezoelectric catalysts were prepared by ball milling, and heterojunctions were constructed. The piezoelectric effect of the piezoelectric materials was used to improve the charge separation and transfer rate, thus preparing a composite catalyst with highly efficient synergistic catalytic performance in the range of 90-400℃.

Benefits of technology

This method achieves highly efficient synergistic catalytic degradation of nitrogen oxides and chlorinated organic compounds over a wide temperature range, reduces dielectric constant and electron transfer resistance, improves catalyst performance, simplifies preparation process, and reduces cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120393996A_ABST
    Figure CN120393996A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite catalyst for synergistically denitrifying and removing chlorine-containing organic matters, which comprises the following steps: adding a raw material, a piezoelectric material and nitrate of transition metal into a ball-milling tank according to a mass ratio of 1: (0.25-4) for ball-milling to obtain a ball-milled material A; drying the ball-milled material A in a vacuum oven to obtain a material B; and calcining the material B in an air atmosphere to obtain the composite catalyst. The nitrate of the transition metal is mixed nitrate of manganous nitrate and one of cerous nitrate, cobalt nitrate and nickel nitrate. The high dielectric constant and electron transfer resistance of the composite catalyst are reduced by constructing a heterojunction through ball milling, the transfer rate of holes and electrons is increased, and the quantity of electric charges participating in a surface redox reaction is increased, so that the concerted catalytic degradation performance of pollutants in waste incineration flue gas is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation, and specifically relates to a composite catalyst for synergistic denitrification and dechlorinated organic matter removal, a preparation method thereof, and an application thereof. Background Art

[0002] With the rapid development of China's economic society, incineration has become the main method for garbage disposal, and the emission standards for garbage incineration flue gas are becoming increasingly strict. It is urgent to strengthen the control of incineration pollutants. In the existing pollutant treatment processes, a single module is often used to treat a single pollutant, resulting in a large number of modules in series, large space requirements, and high investment costs. Therefore, the study of the synergistic removal of nitrogen oxides and chlorinated organic compounds in low-temperature incineration flue gas is an inevitable trend in the development of this field, and the development of a synergistic catalyst with good low-temperature activity has become an urgent need for the purification of incineration flue gas. However, problems such as poor synergistic performance and low selectivity currently existing greatly restrict the rapid development of synergistic catalysis technology. In response to this problem, methods such as doping metal oxides and separating active sites have been adopted in current research for certain improvement, but there is still a large room for development.

[0003] In recent years, it has been found that the built-in electric field generated by the piezoelectric effect is conducive to promoting charge separation and transfer. BaTiO3 is a typical ABO3-type perovskite with excellent piezoelectric properties and thermal stability. Under the action of external mechanical force, charges will be induced on the surface of BaTiO3 due to the piezoelectric effect. If the electric potential of these charges exceeds a certain value, they will participate in the corresponding reactions. Metal oxides have high dielectric constants and electron transfer resistances, and the transfer rates of holes and electrons are slow and they are repeatedly recombined, which will reduce the amount of charge participating in the surface redox reaction, thus significantly inhibiting the synergistic catalytic performance. Therefore, inducing the formation of a heterojunction between piezoelectric materials and metal oxides by ball milling is an attractive strategy.

[0004] Although there have been many studies on improving the performance of catalysts by constructing heterojunctions, these improvements in catalytic performance are mainly achieved through the synergistic effect of light and pressure fields. However, this type of method cannot effectively solve the problem of poor catalytic performance in the absence of light or pressure fields. This patent proposes a method for preparing a high-performance composite catalyst through the piezoelectric effect of piezoelectric materials during ball milling, realizing synergistic denitrification and dechlorinated organic matter removal in a temperature field. Summary of the Invention

[0005] In order to solve at least one of the above problems, the present invention provides a composite catalyst for synergistic denitrification and dechlorinated organic matter removal, a preparation method thereof, and an application thereof. The composite catalyst is a metal oxide-based piezoelectric catalyst material and can be used for the synergistic degradation of multiple pollutants in garbage incineration flue gas in a wide temperature range of 90 - 400 °C.

[0006] To achieve the above object, the present invention adopts the following technical means: The first aspect of the present invention provides a preparation method of a composite catalyst for synergistic denitrification and dechlorinated organic matter, comprising the following steps: S1. Add raw materials: a piezoelectric material and a nitrate of a transition metal into a ball mill tank according to a mass ratio of 1:(0.25 - 4) for ball milling to obtain ball-milled material A; S2. Dry the ball-milled material A in a vacuum oven to obtain material B; S3: Calcinate the material B in an air atmosphere to obtain the composite catalyst; The nitrate of the transition metal is a mixed nitrate of manganese nitrate and one or more of cerium nitrate, cobalt nitrate and nickel nitrate.

[0007] In some embodiments of the present invention, preferably, the mass ratio of the piezoelectric material to the nitrate of the transition metal is 1:4.

[0008] In some embodiments of the present invention, the piezoelectric material is one of barium titanate, lithium niobate and potassium sodium niobate.

[0009] In some embodiments of the present invention, in the mixed nitrate, the mass fraction of manganese nitrate is 35 - 45%.

[0010] In some embodiments of the present invention, in step S1, the mass ratio of the raw materials to the ball milling beads in the ball mill tank is (0.5 - 2.5):(10 - 15), and the raw materials account for 1 / 3 of the volume of the ball mill tank.

[0011] In some embodiments of the present invention, in step S1, the ball milling conditions of the ball mill tank are: the ball milling speed is 300 - 600 r / min, and the ball milling time is 2 - 6 hours.

[0012] In some embodiments of the present invention, in step S2, the drying conditions are: the drying temperature is 90 - 110 °C, and the drying time is 10 - 24 hours.

[0013] In some embodiments of the present invention, in step S3, the calcination conditions are: the calcination temperature is 300 - 500 °C, and the calcination time is 2 - 5 hours.

[0014] The second aspect of the present invention provides a composite catalyst prepared by the method according to the first aspect.

[0015] The third aspect of the present invention provides an application of the composite catalyst according to the second aspect in synergistic catalytic degradation of gaseous pollutants, and the gaseous pollutants include nitrogen oxides and dechlorinated organic matter. It can be applied to the degradation of atmospheric pollutants, and can also be applied to the synergistic catalysis of multiple pollutants in waste incineration flue gas.

[0016] In some embodiments of the present invention, the temperature range for the synergistic catalytic degradation by the composite catalyst is 90 - 400 °C.

[0017] In some embodiments of the present invention, the application process is as follows: The composite catalyst is placed in a programmed temperature fixed bed, and the synergistic catalytic degradation of nitrogen oxides and chlorinated organic compounds is carried out within the temperature range of 90 - 400 °C.

[0018] Advantages of the present invention Compared with the prior art, the present invention has the following advantages: The present invention provides a metal oxide-based piezoelectric catalyst, which is prepared by high-temperature sintering of a mixture material obtained by ball milling. The ball milling process is simple and can be mass-produced on a large scale; in this application, a heterojunction is constructed by ball milling to reduce the relatively high dielectric constant and electron transfer resistance of the metal oxide catalyst, improve the transfer rate of holes and electrons, and increase the amount of charge participating in the surface redox reaction, thereby enhancing the synergistic catalytic degradation performance of pollutants in waste incineration flue gas. The preparation method of the present invention has the characteristics of simple process, safety, environmental protection, and low cost, and the catalyst exhibits high synergistic catalytic performance. Within the temperature range of 90 - 400 °C, it can simultaneously catalytically degrade nitrogen oxides and chlorinated organic compounds. Description of the drawings

[0019] Figure 1 Shows the scanning electron microscope photograph of the catalyst prepared in Example 1 of the present invention; Figure 2 Shows the transmission electron microscope photograph of the catalyst prepared in Example 2 of the present invention; Figure 3 Shows the scanning electron microscope photograph of the catalyst prepared in Comparative Example 1 of the present invention; Figure 4 Shows the scanning electron microscope photograph of the catalyst prepared in Comparative Example 2 of the present invention; Figure 5 Shows the scanning electron microscope photograph of the catalyst prepared in Comparative Example 3 of the present invention; Figure 6 Shows the degradation efficiency diagram of 1,2-dichlorobenzene for the synergistic catalytic degradation of chlorinated organic compounds and NOx by the composite catalysts prepared in Examples 1 - 7 of the present invention; Figure 7 Shows the NOx degradation efficiency diagram for the synergistic catalytic degradation of chlorinated organic compounds and NOx by the composite catalysts prepared in Examples 1 - 7 of the present invention; Figure 8 Shows the degradation efficiency diagram of 1,2-dichlorobenzene for the synergistic catalytic degradation of chlorinated organic compounds and NOx by the catalysts prepared in Comparative Examples 1 - 6 of the present invention; Figure 9The NOx degradation efficiency diagrams of the catalysts prepared in Comparative Examples 1-6 of the present invention for synergistically catalyzing chlorinated organic compounds and NOx are shown.

[0020] Figure 10 The electronic band structures of Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 are shown. Specific Embodiments

[0021] The following examples are used herein to demonstrate the preferred embodiments of the present invention. Those skilled in the art will understand that the techniques disclosed in the following examples represent techniques that the inventors have found can be used to implement the present invention, and thus can be regarded as preferred embodiments for implementing the present invention. However, those skilled in the art should understand from this specification that many modifications can be made to the specific embodiments disclosed herein, and still obtain the same or similar results without departing from the spirit or scope of the present invention.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. The materials cited herein and their citations will be incorporated by reference. Those skilled in the art will recognize or be able to learn many equivalent techniques to the specific embodiments of the invention described herein through routine experimentation. These equivalents will be included in the claims.

[0023] The technical solutions of this application will be further described in detail below in conjunction with specific embodiments.

[0024] Example 1 A preparation method of a TB-MnCe2:8 composite catalyst includes the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6; weigh 3 g of barium titanate according to a mass ratio of 2:8 with a metal oxide, and place them together in a ball milling jar. The ball milling parameters are set as a ball-to-powder mass ratio of 15:1, where the zirconia balls are 5 mm:10 mm = 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as TB-MnCe2:8.

[0025] Example 2 A preparation method of a TB-MnCe4:6 composite catalyst includes the following steps: Weigh 3.6 g of manganese nitrate and 5.4 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 6 g of barium titanate according to a mass ratio of 4:6 for barium titanate and metal oxide, and place them together in a ball milling jar. The ball milling parameters are set as a ball-to-powder mass ratio of 15:1, where the zirconia balls of 5 mm:10 mm = 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as TB-MnCe4:6.

[0026] Example 3 A preparation method of a TB-MnCe6:4 composite catalyst includes the following steps: Weigh 2.4 g of manganese nitrate and 3.6 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 9 g of barium titanate according to a mass ratio of 6:4 for barium titanate and metal oxide, and place them together in a ball milling jar. The ball milling parameters are set as a ball-to-powder mass ratio of 15:1, where the zirconia balls of 5 mm:10 mm = 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as TB-MnC6:4.

[0027] Example 4 A preparation method of a TB-MnCe8:2 composite catalyst includes the following steps: Weigh 0.6 g of manganese nitrate and 2.4 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 12 g of barium titanate according to a mass ratio of 8:2 for barium titanate and metal oxide, and place them together in a ball milling jar. The ball milling parameters are set as a ball-to-powder mass ratio of 15:1, where the zirconia balls of 5 mm:10 mm = 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as TB-MnCe8:2.

[0028] Example 5 A preparation method of a TB-MnCo2:8 composite catalyst includes the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 3 g of barium titanate according to a mass ratio of 2:8 for barium titanate and metal oxide. Place them together in a ball milling jar, where the ball milling parameters are set as a ball-to-powder mass ratio of 15:1, with zirconia balls of 5 mm:10 mm = 1:1, a rotation speed of 600 rpm, and a time of 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as TB-MnCo2:8.

[0029] Example 6 A preparation method of a Ni-MnCe2:8 composite catalyst includes the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 3 g of barium titanate according to a mass ratio of 2:8 for lithium niobate and metal oxide. Place them together in a ball milling jar, where the ball milling parameters are set as a ball-to-powder mass ratio of 15:1, with zirconia balls of 5 mm:10 mm = 1:1, a rotation speed of 600 rpm, and a time of 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as Ni-MnCe2:8.

[0030] Example 7 A preparation method of a NiK-MnCe2:8 composite catalyst includes the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6 for manganese nitrate and cerium nitrate; weigh 3 g of barium titanate according to a mass ratio of 2:8 for potassium sodium niobate and metal oxide. Place them together in a ball milling jar, where the ball milling parameters are set as a ball-to-powder mass ratio of 15:1, with zirconia balls of 5 mm:10 mm = 1:1, a rotation speed of 600 rpm, and a time of 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite catalyst, denoted as NiK-MnCe2:8.

[0031] Comparative Example 1 A preparation method of a MnCe metal oxide catalyst comprises the following steps: Weigh 6 g of manganese nitrate and 9 g of cerium nitrate according to a mass ratio of 4:6, and place them together in a ball milling tank. The ball milling parameters are set as follows: the mass ratio of balls to powder is 15:1, the ratio of 5-mm zirconia balls to 10-mm zirconia balls is 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the metal oxide catalyst, denoted as MnCe.

[0032] Comparative Example 2 A preparation method of a SiO2-MnCe metal oxide-based piezoelectric catalyst comprises the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6; weigh 3 g of silicon dioxide according to a mass ratio of 8:2 of metal oxide to silicon dioxide, and place them together in a ball milling tank. The ball milling parameters are set as follows: the mass ratio of balls to powder is 15:1, the ratio of 5-mm zirconia balls to 10-mm zirconia balls is 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the metal oxide catalyst, denoted as SiO2-MnCe.

[0033] Comparative Example 3 A preparation method of a TBH-MnCe2:8 composite piezoelectric catalyst comprises the following steps: Weigh 4.8 g of manganese nitrate and 7.2 g of cerium nitrate according to a mass ratio of 4:6; weigh 3 g of barium titanate according to a mass ratio of 2:8 of potassium sodium niobate to metal oxide, dissolve them together, and prepare the preliminarily ball-milled material A by the co-precipitation method. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the composite piezoelectric catalyst, denoted as TBH-MnCe2:8.

[0034] Comparative Example 4 A preparation method of a piezoelectric catalyst comprises the following steps: Place 15 g of barium titanate in a ball milling tank. The ball milling parameters are set as follows: the mass ratio of balls to powder is 15:1, the ratio of 5-mm zirconia balls to 10-mm zirconia balls is 1:1, the rotation speed is 600 rpm, and the time is 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry it for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the piezoelectric catalyst, denoted as TB.

[0035] Comparative Example 5 A preparation method of a piezoelectric catalyst includes the following steps: Place 15 g of lithium niobate in a ball milling jar, where the ball milling parameters are set as a ball-to-powder mass ratio of 15:1, with zirconia balls of 5 mm:10 mm = 1:1, a rotation speed of 600 rpm, and a time of 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the piezoelectric catalyst, denoted as Ni.

[0036] Comparative Example 6 A preparation method of a piezoelectric catalyst includes the following steps: Place 15 g of potassium sodium niobate in a ball milling jar, where the ball milling parameters are set as a ball-to-powder mass ratio of 15:1, with zirconia balls of 5 mm:10 mm = 1:1, a rotation speed of 600 rpm, and a time of 6 h to obtain the preliminarily ball-milled material A. Place material A in a vacuum oven at 100 °C and dry for 10 hours to obtain material B. Calcinate material B in a muffle furnace at 400 °C in an air atmosphere for 3 hours to obtain the piezoelectric catalyst, denoted as NiK.

[0037] Performance test and result analysis (1) The catalytic degradation performance of NOx and 1,2-dichlorobenzene of the TB-MnCe catalysts prepared in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1, Comparative Example 2 was tested by a temperature-programmed fixed bed. After granulating the prepared catalysts, weigh 0.6 g of the catalyst with a particle size of 40 mesh - 60 mesh and mix it with 0.4 g of quartz sand with the same particle size, then load it into a quartz tube. Place the quartz tube on a temperature-programmed fixed bed. Introduce 200 ppm of 1,2-dichlorobenzene, 400 ppm of NO, 400 ppm of NH3, 10% O2 / N2, with a flow rate of 300 mL / min.

[0038] (2) The above Examples 1 - 7 are composite catalysts prepared by the method of the present invention under different conditions. Among them, the SEM image of the catalyst prepared in Example 1 is as Figure 1 shown, the SEM image of the catalyst prepared in Example 2 is as Figure 2 shown, the SEM image of the catalyst prepared in Comparative Example 1 is as Figure 3 shown, the SEM image of the catalyst prepared in Comparative Example 2 is as Figure 4 shown, the SEM image of the catalyst prepared in Comparative Example 3 is as Figure 5 shown.

[0039] From the Figures 1 - 2 SEM images, it can be seen that the composite catalyst synthesized by the ball milling method presents an orderly and regular polygon morphology, with relatively uniform size and in the nanometer scale.

[0040] (3)We carried out the degradation experiments of 1,2-dichlorobenzene and NOx with the catalysts prepared in Examples 1-7. The conversion rates of 1,2-dichlorobenzene and NOx at different temperatures are shown in Table 1, Table 2 and Figure 6 , Figure 7 as shown below.

[0041] Table 1 Conversion rates of the catalysts in Examples 1-7 for 1,2-dichlorobenzene at different temperatures (%)

[0042] Table 2 Conversion rates of the catalysts in Examples 1-7 for NOx at different temperatures (%)

[0043] It can be Figure 6 seen that for the composite catalysts obtained by the ball milling method in Examples 1-4, their low-temperature 1,2-dichlorobenzene conversion effect is better. Among them, when the ratio of manganese-cerium metal oxide to barium titanate is 8:2, the effect is better than other ratios. In Example 5, the ball milling method was used, and one of the metal salts, manganese nitrate, was replaced with cerium nitrate to prepare the composite catalyst. In Examples 6-7, the ball milling method was used for catalysis, and the piezoelectric material barium titanate was replaced with lithium niobate and potassium sodium niobate respectively, which had excellent degradation effects on 1,2-dichlorobenzene. It can be Figure 7 seen that for the composite catalysts obtained by the ball milling method in Examples 1-4, their NO degradation effect is better, with higher conversion rates at low temperatures and a wider temperature range. The overall trend is similar to that of 1,2-dichlorobenzene.

[0044] (4)We carried out the degradation experiments of 1,2-dichlorobenzene and NOx with the catalysts prepared by the ball milling method in Comparative Examples 1-6. The conversion rates of 1,2-dichlorobenzene and NOx at different temperatures are shown in Table 3, Table 4 and Figure 8 , Figure 9 as shown below.

[0045] Table 3 Conversion rates of the catalysts in Comparative Examples 1-6 for 1,2-dichlorobenzene at different temperatures (%)

[0046] Table 4 Conversion rates of the catalysts in Comparative Examples 1-6 for NOx at different temperatures (%)

[0047] Comparative Examples 1-3 are the pure manganese-cerium metal oxide catalyst MnCe obtained by ball milling, the catalyst SiO2-MnCe obtained by replacing the piezoelectric material with ordinary silica by ball milling, and the catalyst TBH-MnCe prepared by using manganese-cerium metal oxide and the impregnation method. Compared with Figure 6, the degradation efficiency of 1,2-dichlorobenzene by the catalyst in the comparative example is poor at low temperatures. Comparative examples 4-6 are catalysts obtained by ball-milling pure piezoelectric materials, and from Figure 8 it can be seen that their overall effect is significantly lower than that of the catalyst without adding metal oxides. From Figure 9 it can be seen that the NO degradation effect of the catalyst in the comparative example is significantly lower than that of the catalyst in the example. Specifically, the low-temperature degradation efficiency of NO is poor and the temperature range is narrow.

[0048] (5) For the materials obtained in Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, the band gap and the valence band top VB of the materials were obtained by ultraviolet diffuse reflection and VBXPS tests respectively, and the conduction band bottom CB was calculated. The schematic diagram of the energy levels of the obtained materials is as shown in Figure 10 shown.

[0049] From the comparison of the schematic diagrams of the energy levels, it can be seen that the band gap of TB-MnCe in Example 1 is the narrowest, and the narrower band gap promotes more effective charge separation and transfer. This also coincides with the previous performance test results.

[0050] All documents mentioned in the present invention are cited herein as references, as if each document was cited individually as a reference. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by this application.

Claims

1. A preparation method of a composite catalyst for synergistic denitrification and dechlorinated organic compound removal, characterized in that, It includes the following steps: S1. Add raw materials: a piezoelectric material and nitrates of transition metals into a ball milling jar at a mass ratio of 1:(0.25 - 4) for ball milling to obtain ball milled material A; S2. Place the ball milled material A in a vacuum oven for drying to obtain material B; S3: Calcinate the material B in an air atmosphere to obtain the composite catalyst; The nitrates of the transition metals are mixed nitrates of manganese nitrate and one or more of cerium nitrate, cobalt nitrate and nickel nitrate.

2. The method according to claim 1, characterized in that: The piezoelectric material is one of barium titanate, lithium niobate, and sodium potassium niobate.

3. The method according to claim 1, characterized in that: In the mixed nitrates, the mass fraction of manganese nitrate is 35 - 45%.

4. The method according to claim 1, characterized in that: In step S1, the mass ratio of the raw materials to the ball milling beads in the ball milling jar is (0.5 - 2.5):(10 - 15), and the raw materials account for 1 / 3 of the volume of the ball milling jar.

5. The method according to claim 1, wherein: In step S1, the ball milling conditions of the ball milling jar are: ball milling speed 300 - 600 r / min, and ball milling time 2 - 6 hours.

6. The method according to claim 1, characterized in that: In step S2, the drying conditions are: drying temperature 90 - 110 °C, and drying time 10 - 24 hours.

7. The method according to claim 1, wherein: In step S3, the calcination conditions are: calcination temperature 300 - 500 °C, and calcination time 2 - 5 hours.

8. A composite catalyst prepared by the method according to any one of claims 1 - 7.

9. Use of the composite catalyst according to claim 8 in the synergistic catalytic degradation of flue gas pollutants, characterized in that: The flue gas pollutants include nitrogen oxides and chlorine - containing organic compounds.

10. The application according to claim 9, wherein: The temperature range for the synergistic catalytic degradation of the composite catalyst is 90 - 400 °C.

Citation Information

Patent Citations

  • Denitration catalyst as well as preparation method and application thereof

    CN113318748A

  • Low-temperature adsorption catalyst and preparation method thereof

    CN116273150A

  • Sulfur-water-resistant Mn-based low-temperature denitration catalyst as well as preparation method and application thereof

    CN117244560A

  • Adsorbent catalyst

    US20020013226A1

  • Hybrid synergistically-enhanced low-temperature SCR denitration catalyst and preparation method therefor

    WO2021180142A1